2019
DOI: 10.1186/s10033-019-0344-8
|View full text |Cite
|
Sign up to set email alerts
|

Force Analysis and Curve Design for Laying Pipe in Loop Laying Head of Wire Rod Mills

Abstract: Laying head is a high-precision engineering device in hot-rolled high speed wire rod production line. Previously research works are focused on the laying pipe wear-resisting. Laying pipe curve design method based on wire rod kinematics and dynamics analyses are not reported before. In order to design and manufacture the laying pipe, the motion and force process of the wire rod in the laying pipe should be studied. In this paper, a novel approach is proposed to investigate the force modeling for hot-rolled wire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Especially, Japan has gradually developed and applied the pipe roof method, and invented some construction methods for passing through railways, such as the under railway road tunnelling (URT) method 2,3 , the prestressed concrete roof (PCR) method 4 , the high-speed element pull and jointed element structure (HEP & JES) method [5][6][7] , etc. Through the site instrumentation, experiment and theoretical analysis, it is found that pipe roof can reduce soil disturbance and ground settlement [8][9][10] . With the advantage of the settlement control of the pipe roof, the roof-box jacking (RBJ) method was formed by combining the pipe roof method and the box culvert jacking method 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, Japan has gradually developed and applied the pipe roof method, and invented some construction methods for passing through railways, such as the under railway road tunnelling (URT) method 2,3 , the prestressed concrete roof (PCR) method 4 , the high-speed element pull and jointed element structure (HEP & JES) method [5][6][7] , etc. Through the site instrumentation, experiment and theoretical analysis, it is found that pipe roof can reduce soil disturbance and ground settlement [8][9][10] . With the advantage of the settlement control of the pipe roof, the roof-box jacking (RBJ) method was formed by combining the pipe roof method and the box culvert jacking method 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The PPM is a trenchless pre-reinforcement technique applied before shallow underground excavation, which can be carried out on sensitive ground with various facilities nearby, importantly without affecting ground traffic [8]. Therefore, the PPM has now become an auxiliary method widely used in the trenchless construction of underground structures for the protection of soft soil foundation areas in various countries [6,[9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…An important condition for achieving compliance with the properties of the product to customer requirements in the production of high-quality steels, including tube steels is observance with thermo mechanical regimes throughout the mill line. For example, the formation of the required grain size of austenite and the separation of niobium and vanadium carbonitrides require strict adherence to temperature and mode of the thickness reduction over the passes [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%